Swallowing dysfunction following endotracheal intubation: Age matters. Issue 24 (June 2016) - Tsai, Min-Hsuan; Ku, Shih-Chi; Wang, Tyng-Guey; Hsiao, Tzu-Yu; Lee, Jang-Jaer; Chan, Ding-Cheng; Huang, Guan-Hua; Chen, Cheryl Chia-Hui
Abstract : Abstract: To evaluate postextubation swallowing dysfunction (PSD) 21 days after endotracheal extubation and to examine whether PSD is time-limited and whether age matters. For this prospective cohort study, we evaluated 151 adult critical care patients (≥20 years) who were intubated for at least 48 hours and had no pre-existing neuromuscular disease or swallowing dysfunction. Participants were assessed for time (days) to pass bedside swallow evaluations (swallow 50 mL of water without difficulty) and to resume total oral intake. Outcomes were compared between younger (20–64 years) and older participants (≥65 years). PSD, defined as inability to swallow 50 mL of water within 48 hours after extubation, affected 92 participants (61.7% of our sample). At 21 days postextubation, 17 participants (15.5%) still failed to resume total oral intake and were feeding-tube dependent. We found that older participants had higher PSD rates at 7, 14, and 21 days postextubation, and took significantly longer to pass the bedside swallow evaluations (5.0 vs 3.0 days; P = 0.006) and to resume total oral intake (5.0 vs 3.0 days; P = 0.003) than their younger counterparts. Older participants also had significantly higher rates of subsequent feeding-tube dependence than younger patients (24.1 vs 5.8%; P = 0.008). Excluding patients with pre-existing neuromuscular dysfunction, PSD is common and prolonged. Age matters in the time needed to recover. Swallowing and oral intake should be monitored and interventions made, if needed, in the first 7 to 14 days postextubation, particularly for older patients.